Diagnostic Value of Apparent Diffusion Coefficient (ADC) and Tumor Size Based on Magnetic Resonance Imaging (MRI) to Determine Malignant Posterior Fossa Brain Tumors in Children - Ivon Indriyanti Santoso; Pande Putu Yuli Anandasari; Ni Nyoman Margiani; I Gde Raka Widiana (Eduvest - Journal of Universal Studies, 2025)
Posterior fossa tumors in children are a diagnostic challenge that requires early and appropriate treatment. This study aims to evaluate the diagnostic value of Apparent Diffusion Coefficient (ADC) and tumor size using Magnetic Resonance Imaging (MRI) in distinguishing malignant and benign tumors in the posterior fossa of children. The research method uses a retrospective approach with analysis of medical records of pediatric patients undergoing MRI and histopathology examinations at Ngoerah Hospital Denpasar. The results showed that the ADC value of ≤834.6 mm²/s had a sensitivity of 91.3%, a specificity of 70.3%, and an accuracy of 78.0%. Meanwhile, the tumor size >13.2 cm³ has a sensitivity of 91.3%, specificity of 51.8%, and accuracy of 68.0%. The combination of these two parameters resulted in a sensitivity of 87.5%, a specificity of 96.1%, and an accuracy of 92.0%, indicating a significant improvement in diagnostic accuracy. Thus, the simultaneous use of ADC values and tumor size is an effective approach in detecting malignant posterior fossa tumors in children, supporting more accurate diagnosis and appropriate clinical treatment.